Resposta da cana-de-açúcar à aplicação da escória de siderurgia como corretivo de acidez do solo - Prado, R. M. [UNESP]; Fernandes, F. M. [UNESP] (Sociedade Brasileira de Ciência do Solo, 2001)
High acidity predominates in southeastern and midwestern Brazilian soils, where the largest area of sugar cane plantations is concentrated. Large amounts of slag, a steel-industry residue containing nutrients such as calcium and magnesium and acting as acidity corrective agents, are also present in the region. This study aimed to evaluate different base saturation levels using slag as a soil corrective agent. This material was compared to calcitic limestone to analyze acidity neutralization and certain chemical soil properties, as well as sugarcane response during the first two cuts. Thus, an experiment was carried out using sugarcane variety SP 80-1842 during 1998/1999 and 1999/2000. The treatments were arranged in a randomized block design, with four replications, consisting of two sources of corrective agents-calcitic limestone and slag - and four correction levels, estimated by the base saturation method (V%): control without correction and V% correction of 50,75 and 100. It was concluded that the limestone and slag application had a similar effect on the correction of the soil acidity as well as on the increase of calcium and magnesium concentrations of the soil and base saturation. Limestone and slag applications had a quadratic and linear effect, respectively, on culm production and number of millable stalk.

A acidez elevada dos solos da região sudeste e centro-oeste do Brasil predomina onde se concentra a maior área cultivada com cana-de-açúcar. Grandes depósitos de escória de siderurgia, que contêm nutrientes como cálcio e magnésio e apresentam ação corretiva de acidez, localizam-se também naquelas regiões. O presente trabalho objetivou avaliar diferentes níveis de saturação por bases, utilizando como corretivo do solo a escória de siderurgia, comparando-a com calcário calcítico, nas alterações de alguns atributos químicos do solo, bem como na resposta da cana-de-açúcar, durante os dois primeiros cortes. Para isto, foi realizado um experimento com a cana-de-açúcar, variedade SP 80-1842, nos anos agrícolas 98/99 e 99/00. Os tratamentos, dispostos em blocos casualizados em esquema fatorial com quatro repetições, constaram de duas fontes de corretivos, calcário calcítico e escória de siderurgia, e quatro níveis de correção, estimados pelo método da saturação por bases (V%): testemunha sem correção e correção para V% de 50, 75 e 100. Concluiu-se que os efeitos da aplicação do calcário e da escória de siderurgia foram semelhantes na correção da acidez do solo, na elevação da concentração de cálcio e magnésio do solo e na saturação por bases. As doses de calcário proporcionaram efeito quadrático sobre a produtividade e perfilhamento da cana-de-açúcar, enquanto as de escória resultaram em resposta linear.
Response of sugar cane to application of slag as a corrective agent for acidity in soil
Keywords: silicato; calcário calcítico; saturação por bases; Saccharum L; silicate; calcitic limestone; base saturation; Saccharum L.